A novel intracellular signal amplification strategy for the quantification of ATP in single cells by microchip electrophoresis with laser-induced fluorescence detection - Chen, Shengyu; Zhao, Jingjin; Yang, Xing; Zhao, Shulin; Liu, Yi-Ming (Chemical communications (Cambridge, England), 2020)
An intracellular signal amplification strategy was developed for the quantification of ATP in single cells by microchip electrophoresis with laser-induced fluorescence detection. By using the method proposed, intracellular ATP levels in single HeLa, HepG2 and HL-7702 cells were found to be in the range of 30-150, 30-140, and 19-120 fmol per cell, respectively. An intracellular signal amplification strategy was developed for the quantification of ATP in single cells by microchip electrophoresis laser-induced fluorescence detection.